(untitled) (Journal of Academic Research, 2021)
The present study aims to identify the prediction of the academic engagement in the light of the academic self-concept, and the academic aspiration of the students of the Faculty of Education, Misurata University, as well as identifying of the level of the academic engagement, academic self-concept, and the academic aspiration. It also intends to identify the differences between the averages of the degrees of each scale of the academic engagement, academic self-concept, and academic aspiration; condescending to the variable: gender. The sample of the current study consists of (181) male and female students, including (37) male and (144) female students of the Faculty of Education, Misurata University, of the first semester for the academic year: (2019/2020). The researchers have used the academic engagement scale, the academic and the self-concept scale, prepared by researchers. The academic aspiration scale has been prepared by Mohamed Moawad and Sayed Abdel-Azim (2005). The researchers have also used the following statistical methods: arithmetic averages and the standard deviations, the value of (T) for one sample, the value of (T) for two independent samples, and the analysis of the variance of the declination. The results of the study have shown that : The categories level of the scale of each of the academic engagement, academic self-concept, and academic aspiration. The total score for the standards exceeds the students of the Faculty of Education, Misurata University, according to their estimates of themselves based on the assumption level. The results of the study have also shown that: There are no differences between the averages of the scores for the scale of the academic engagement, academic self-concept, and the academic aspiration, depending on the gender variable. The results of the study have also shown that there is no effect of independent variables: (the academic self-concept and the academic aspiration) on the dependent variable: (the academic engagement).